EFFICACY OF PLAY THERAPY INTERVENTIONS ON BREAKUP DISTRESS AND DEPRESSIVE SYMPTOMATOLOGY AMONG INDIVIDUALS WITH NON-MARITAL BREAKUP - Manal Shekhani, Sheeba Farhan & Zara Israr (Pakistan Journal of Psychology, 2021)
The current research examined the efficacy of play therapy interventions on breakup distress and symptoms of depression among individuals with non-marital breakup. A quantitative Pretest-Posttest quasi experimental research design was used. A purposive sampling technique was used to approach emerging adults (N=18) with an age range of 18-30 years with mean age of 24.27 (± SD=2.76). The data was collected through the Breakup Distress Scale (Field et al., 2010) and the Center for Epidemiologic Studies Depression Scale (Radloff, 1977). The intervention included a 7-session plan following the theoretical framework of Rando’s Six R’s of mourning. The results of Paired Sample and Independent Sample t-tests indicate a significant difference in break-up distress for the experimental group. However, for depressive symptomatology no significant difference was obtained for experimental group. Conclusively, play therapy was effective in reducing break up distress but not much change was seen in depressive symptomology. These findings have significant clinical and research implications